Pengaruh Brand Awarenes Dan Online Customer Review Terhadap Keputusan Pembelian Pada Market Place Shopee Studi Kasus Pada Masyarakat Dusun III Batang Kuis Deli Serdang - Nasution, Ferdi Salim; Utama, Indra; Hidayat, Toni; Siregar, Horia; Safina, Wan Dian (Movere Journal, 2024)
Using the Shopee marketplace, this research tries to ascertain how brand awarenes and online customer reviews influence purchasing decisions in consumers in Dusun III Batang Kuis Deli Serdang. This study uses quantitative descriptive methodology and collects data through questionnaires, interviews, and observations. The population targeted by this study is everyone who uses the Shopee application, especially those who live in Dusun III Batang Kuis Deli Serdang. Respondents of this study will be selected using non-probability sampling and using the Slovin theory, namely 100 samples encountered during the research. Using the SPSS 22 application, multiple linear regression analysis was used to test the data collected for this study. The results of this study indicate that the calculated F value of 298,258 is greater than the F table of 3.09, which means that simultaneously there is an influence on the variables brand awareness (X1) and online costumer review (X2) on purchasing decisions (Y) in the shopee marketplace. Partially, it can be seen that the variables brand awareness (X1) and online costumer review (X2) have an effect on purchasing decisions, namely the brand awareness variable (X1) of 3.966 is greater than the t table of 1.660 and online costumer review (X2) of 4.714 is greater than the t table of 1.660. Based on the results seen from the coefficient of determination, the variables brand awareness (X1) and online costumer review (X2) have an effect with an R2 value of 0.860 or 8.60%.